The ultrasound study of the optic canal for detecting raised intracranial pressure (a literature review and critical analysis) - M. I. Andreytseva; S. S. Petrikov; L. T. Khamidova; A. A. Solodov (Неотложная медицинская помощь, 2019)
Intracranial hypertension (ICH) is a frequent and serious complication that occurs in pa-tients with severe traumatic brain injury (TBI) and nontraumatic brain damage. Persistent ICH significantly worsens the prognosis of the disease course and increases the risk of adverse outcomes. In this regard, one of the main tasks of intensive care of patients with intracranial bleeding (ICB) is diagnosis and timely management of ICH. The gold standard is invasive intracranial pressure (ICP) monitoring. The advantages of direct measurement of ICP include accuracy and continuity of registration. The disadvantages are the invasiveness of the method, high cost, the risk of developing infectious and hemorrhagic complications and possible dislocation of sensors. It is necessary to search for a method of non-invasive assessment of the level of ICH most correlated with the data of direct measurement of ICP. Ultrasonography of the optic nerve structures can be such an alternative cheap way to assess ICP. Its advantages are the possibility of repeated dynamic use, no need for surgical intervention, simplicity and high accuracy of measurement. However, the results obtained with ultrasound vary, since this method is operator dependent and requires precise adherence to the technique of the study. When the optic nerve ultrasound is performed, a contact gel for ultrasound examinations is applied to the anterolateral surface of the closed upper eyelid, and a scanning plane is displayed behind the eyeball for visualization in the central part of the ultrasound image of the optic nerve, lens and retina. To visualize the vertical course of the ophthalmic artery (and the vertical course of the optic nerve), the color flow Doppler mode is used. The study includes measuring the diameter of the optic nerve and the optic nerve sheath diameter (ONSD). There is subarachnoid space with cerebrospinal fluid between the optic nerve and its sheath. With an increase in intracranial pressure, the expansion of this space occurs, ONSD grows as well. This article contains an analysis of the literature describing the anatomy of the optic nerve and various ultrasound techniques, as well as data from various authors on the threshold value of the optic nerve sheath diameter.